First proteomic analysis of diestrus and anestrus canine oocytes at the germinal vesicle reveals candidate proteins involved in oocyte meiotic competence - Pereira, Leda Maria Costa [UNESP]; Bersano, Paulo Ricardo de Oliveira; Moura, Arlindo de Alencar; Lopes, Maria Denise [UNESP] (Wiley, 2019)
In domestic dogs, oocyte maturation rates are low and the percentage of oocytes that remain in the stage of germinal vesicle (GV) regardless of culture conditions is high. The present study was conducted to characterize the proteome of canine oocyte at the germinal vesicle stage using label-free mass spectrometry. Ovaries were collected from 415 adult domestic dogs and oocytes were divided anestrus and diestrus group. Protein lysates were subjected to quantitative proteomic analysis to identify differentially expressed proteins in different status reproductive. All runs for each sample were performed on an Easy nLC1000 nano-LC chromatograph system directly connected to a quadrupole-type Orbitrap mass spectrometer. For identification of peptides and proteins, raw data of the spectra were loaded into MaxQuant software version 1.5.2.8. Proteomic data were analysed according to gene ontology and a protein–protein interaction network. 312 proteins were identified and grouped according to their biological processes, molecular functions and cellular component. Forty-six differentially expressed proteins among diestrus and control group were associated with at least one GO term in the biological process database. Several proteins involved in the cell cycle, fertilization, regulation of transcription and signalling pathways that are essential for the full development of oocytes and fertilization were expressed. This study identified proteins that were absent, and more or less expressed in different status reproductive. These differentially expressed proteins revealed a framework of molecular reorganization within a GV that renders its competency. This knowledge will enable the identification of target competence biomarkers and thus the establishment of more adequate means of cultivation to improve the M-I and II indexes in this species and also to better understand the physiology of the domestic dog, promoting the development of new reproduction biotechniques.
Keywords: domestic dog; germinal vesicle; meiotic competence; oocyte; proteomic